Picturing resistance : moments and movements of social change from the 1950s to today - Light, Melanie, 1958-; Light, Ken (California : Ten Speed Press, 2020)
"A compelling phographic look at the important moments in the history of progressive resistance in America--from the civil rights movement to present--that will inspire the activists and change-makers of today." -- Back cover
"A compelling photographic history of the important moments of progressive resistance--from the civil rights movement to the present--to inspire the change-makers and activists of today"--
A Vision Takes Hold: 1954-1964 -- Marching toward a Vision of the Future: 1965-1974 -- Exhaustion and Backlash: 1975-1985 -- It's All About the Economy: 1986-1993 -- A New Era in Activism: 1994-2010 -- Activism in a Time of Repression and Upheaval: 2051-2019
Includes bibliographical references (pages 214-228) and index
Keywords: Social movements -- United States -- History; Protest movements -- United States -- History; Social movements -- United States -- Pictorial works; Protest movements -- United States -- Pictorial works; HISTORY / Social History; Protest movements; Social movements; United States; History; Pictorial works; Illustrated works